Management of Patient Primigravida 36-37 Weeks with Chronic Myeloid Leukemia, Anemia, and Thrombocytopenia: A Case Report - Muhammad Farlyzhar Yusuf; Ruddi Hartono (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2021)
Chronic myelogenous leukemia (CML) is a type of cancer caused by a disturbance in the hematopoietic stem cells. CML itself rarely occur on women who are in labor and an advanced procedure in this event has become a special challenge for medics, especially an anesthesiologist. This limits the development of standard anesthesia guidelines, so in this case we describe the incidence of CML in pregnancies performed by Cesarean section with general anesthesia.The first pregnant patient was 36 weeks pregnant; the patient was first diagnosed with Chronic myelogenous leukemia (CML) at the age of 26-28 weeks, at that time the patient complained of frequent dizziness, abdominal pain and weakness, then the patient complained of bleeding gums, and currently the patient complained of nosebleeds. The Bone Marrow shows Conclusion an accelerated phase chronic myeloid leukemia (CML) (suspected atypical CML) with nutritional deficiency. We perform General Anesthesia technique Rapid Sequence Intubation with Regimen Fentanyl 100 mcg, Propofol 80 mg and Rocuronium 50 mg.The patient was admitted to the ICU for 2 days before transferring to intensive care and the patient received intravenous paracetamol 1 gram four times, cefazolin 1 gram twice a day, lansoprazole 30 mg once a day, tranexamic acid 1gr three times a day, and 15 mcg per hour fentanyl contionously. Hemodynamic patients in the ICU are in a stable condition. On the second postoperative day of care, the patient was transferred to the High care ward, then at the third postoperative day the patient's hemodynamics was stable and the patient was transferred to a normal room.